D‐lactate‐selective amperometric biosensor based on the mitochondrial fraction of Ogataea polymorpha recombinant cells. Issue 5 (21st December 2018) - Smutok, Oleh; Karkovska, Maria; Prokopiv, Tetiana; Kavetskyy, Taras; Sibirnyj, Wladimir; Gonchar, Mykhailo
Abstract: During the recent decades, a lot of data about the significance of D‐lactate determination in food technology and quality control have been accumulated. Nowadays, the development of new methods for the determination of D‐lactate is very relevant, especially with regard to biosensors. To construct a D‐lactate‐selective biosensor, we suggest using the mitochondria of recombinant yeast cells of Ogataea ( Hansenula ) polymorpha "tr6" ( gcr1 catX/Δcyb2, prAOX_DLDH ) overproducing D‐lactate: cytochrome c ‐oxidoreductase (DLDH, EC 1.1.2.4) and lacking an L‐lactate‐specific enzyme (flavocytochrome b 2, E.C. 1.1.2.3). The usage of the pure enzyme is problematic due to the complexity of its isolation and stabilization because of the intramembranous localization of DLDH. The enzyme catalyzes D‐lactate oxidation to pyruvate coupled with ferricytochrome c reduction to ferrocytochrome c . The constructed biosensor is characterized by high sensitivity (18.5 А·М −1 ·m −2 ), a low detection limit (3 μM of D‐lactate), wide linear ranges, good selectivity, and sufficient stability. The real samples' analysis of D‐lactate in dairy products was performed, and high correlation of the obtained results with the reference approach (0.7 <  r  < 1) and literature data was demonstrated. Abstract :